2021
DOI: 10.1159/000512351
|View full text |Cite|
|
Sign up to set email alerts
|

Association between Procalcitonin and Acute Kidney Injury in Patients with Bacterial Septic Shock

Abstract: Objective: The objective of this study was to assess the relationship between serum procalcitonin (PCT) and acute kidney injury (AKI) induced by bacterial septic shock. Methods: A retrospective study was designed which included patients who were admitted to the ICU from January 2015 to October 2018. Multiple logistic regression and receiver operating characteristic (ROC) as well as smooth curve fitting analysis were used to assess the relationship between the PCT level and AKI. Results: Of the 1,631 patients s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…It has been widely used as a biomarker for diagnosing bacterial infection and as a promising guideline for antibiotics therapy in sepsis patients. 22 , 23 Although PCT has been demonstrated to be an excellent predictor of AKI development and recovery in a variety of clinical settings, its validity as a predictor of developed S-AKI is still debated. 23 , 24 In this study, we observed that PCT was identified as an independent predictive factor for S-AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely used as a biomarker for diagnosing bacterial infection and as a promising guideline for antibiotics therapy in sepsis patients. 22 , 23 Although PCT has been demonstrated to be an excellent predictor of AKI development and recovery in a variety of clinical settings, its validity as a predictor of developed S-AKI is still debated. 23 , 24 In this study, we observed that PCT was identified as an independent predictive factor for S-AKI.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 Although PCT has been demonstrated to be an excellent predictor of AKI development and recovery in a variety of clinical settings, its validity as a predictor of developed S-AKI is still debated. 23 , 24 In this study, we observed that PCT was identified as an independent predictive factor for S-AKI. More potential explanations of elevated PCT levels in S-AKI have been revealed: (1) S-AKI was caused by elevated blood levels of proinflammatory cytokines and chemokines during the infection and inflammation states; 5 (2) PCT can mediate direct cytotoxicity on mesangial cells by increasing the synthesis of proinflammatory cytokines and causes mesangial cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…According to classical theories, renal hypotension and associated ischemia, as well as a lack of oxygen, are the main pathological mechanisms underlying AKI [ 6 ]. Additionally, PCT has been widely used to diagnose bacterial infections and guide antibiotic therapy in sepsis patients [ 26 , 27 ]. This study had similar findings to previous studies that PCT was more accurate at predicting S-AKI than other inflammatory biomarkers, such as WBC, lymphocytes, monocytes, and NEUT [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common source of patient data was Medical Information Mart for Intensive Care (MIMIC) III, which was used in 15 studies [5 ▪▪ ,7 ▪▪ ,10 ▪▪ ,13–15,16 ▪▪ ,17 ▪▪ ,18,19 ▪▪ –22 ▪▪ ,23 ▪ ,24]. Although most studies ( n = 16) included mixed ICU populations [5 ▪▪ ,7 ▪▪ ,8,10 ▪▪ ,13,16 ▪▪ ,17 ▪▪ ,18,19 ▪▪ –22 ▪▪ ,23 ▪ ,25 ▪▪ ,26 ▪ ,27], there were seven studies focused on sepsis patients [11,12,14,24,28–30], four focused on surgical patients [6,9,31,32 ▪▪ ], one on diabetic ketoacidosis [15], one on haemorrhagic shock [33] and one on acute brain injury [34].…”
Section: Acute Kidney Injury Algorithmsmentioning
confidence: 99%
“…Studies also established baseline sCr from the lowest sCr prior to admission (ranging from 365 days to 1 week prior [25 ▪▪ ,29,30,32 ▪▪ ] or within 7 days prior [24]), mean sCr from 180 to 7 days prior to admission [21 ▪▪ ,26 ▪ ], preoperative sCr [6,31] or the Modified Diet and Renal Disease (MDRD) equation if a measured sCr was not available [9,12,26 ▪ ,30]. Eleven studies did not define baseline sCr [7 ▪▪ ,10 ▪▪ ,11–13,15,20 ▪▪ ,22 ▪▪ ,23 ▪ ,28,33].…”
Section: Acute Kidney Injury Algorithmsmentioning
confidence: 99%